Mak Pika Small Business Coffee Powder Marketing Strategy in Sekalak Village, Seluma Utara District, Seluma Regency - Wisarjan Wisarjan; Sulisti Afriani; Mimi Kurnia Nengsih (Penerbit Jurnal Indonesia, 2021)
The purpose of the study was to find out how the marketing strategy was carried out by the small business coffee powder owner Mak Pika in Sekalak village, Seluma Utara sub-district, Seluma sub-district. The sample in this study was 52 people consisting of 12 employees for internal factors and 40 people for external factors, namely customers from Mak Pika coffee powder. The analytical method used is a SWOT analysis consisting of an Internal Strategy Factor Matrix (IFAS) and an External Strategic Factor Matrix (EFAS). Mak Pika's Small Business Strategy in Sekalak Village, North Seluma District, Seluma Regency supports an aggressive strategy, or SO strategy in the SWOT matrix. The result of the sum of the strengths possessed is 2.02 while the weakness is 1.31, then the internal factor quadrant is 2.02 + 1.31 = 3.33 which means that the ability of Mak Pika's Small Business in Sekalak Village, North Seluma District, Seluma Regency in utilizing strengths and minimize internal weaknesses. The opportunities for this strategy are 1.96 and the threats are 1.47. Then the external factor quadrant is 1.96 +1.47 = 3.43, meaning that the high ability of Mak Pika Small Business in Sekalak Village, North Seluma District, Seluma Regency in taking advantage of opportunities and overcoming threats faced by companies in marketing ground coffee business.